Validity and reliability of the Fitbit Zip as a measure of preschool children’s step count - Kelly Mackintosh (BMJ Open Sport & Exercise Medicine, 2017)
Objectives Validation of physical activity measurement tools is essential to determine the relationship between physical activity and health in preschool children, but research to date has not focused on this priority. The aims of this study were to ascertain inter-rater reliability of observer step count, and interdevice reliability and validity of Fitbit Zip accelerometer step counts in preschool children.Methods Fifty-six children aged 3–4 years (29 girls) recruited from 10 nurseries in North Wales, UK, wore two Fitbit Zip accelerometers while performing a timed walking task in their childcare settings. Accelerometers were worn in secure pockets inside a custom-made tabard. Video recordings enabled two observers to independently code the number of steps performed in 3 min by each child during the walking task. Intraclass correlations (ICCs), concordance correlation coefficients, Bland-Altman plots and absolute per cent error were calculated to assess the reliability and validity of the consumer-grade device.Results An excellent ICC was found between the two observer codings (ICC=1.00) and the two Fitbit Zips (ICC=0.91). Concordance between the Fitbit Zips and observer counts was also high (r=0.77), with an acceptable absolute per cent error (6%–7%). Bland-Altman analyses identified a bias for Fitbit 1 of 22.8±19.1 steps with limits of agreement between −14.7 and 60.2 steps, and a bias for Fitbit 2 of 25.2±23.2 steps with limits of agreement between −20.2 and 70.5 steps.Conclusions Fitbit Zip accelerometers are a reliable and valid method of recording preschool children’s step count in a childcare setting.